RIFM fragrance ingredient safety assessment, 4H-1, 3-benzodioxin, hexahydro-4-methyl-2-(phenylmethyl)-, CAS Registry Number 1373821-23-8. (15th July 2020) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: 4H-1, 3-Benzodioxin, hexahydro-4-methyl-2-(phenylmethyl)-; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.